Evaluation of in vitro properties of 3D micro-macro porous zirconia scaffolds coated with 58S bioactive glass using MG-63 osteoblast-like cells. Issue 7 (July 2019) - Mesquita-Guimarães, J.; Ramos, L.; Detsch, R.; Henriques, B.; Fredel, M.C.; Silva, F.S.; Boccaccini, A.R.
Abstract: A new family of bioceramic scaffolds consisting of zirconia foam-like structures with 58S bioactive glass (BG) coating was developed. Three open-cell structures fabricated by the foam replica method were coated via immersion in a sol-gel solution. The coating technique was optimised controlling the sol viscosity, condensation time, and the number of immersions in order to increase the coating thickness. The scaffolds chemical and structural characteristics were evaluated before in vitro tests, including the Ca/P ratio, crystalline phase composition, pH change, pore diameter and microporosity of the scaffolds struts. In vitro tests were performed by culturing MG-63 human osteoblast-like cells. An increase in cell proliferation of 100% was found with the decrease in pore size from 700 to 120 μm. Also, with the presence of the 58S-BG coating, an increase of cell proliferation was reached, which indicates the positive effect of the BG coating on the otherwise bioinert ceramic scaffold.